2003
DOI: 10.1159/000070632
|View full text |Cite
|
Sign up to set email alerts
|

Normal Values of Short-Wavelength Automated Perimetry

Abstract: Background: The purpose of this study was to evaluate short-wavelength automated perimetry (SWAP, i.e., blue-yellow) in normal volunteers and to review the current normal values provided by the manufacturer. Methods: 28 eyes of 28 normal subjects (age range 21–48 years, mean age 36.5 years) had SWAP (Octopus 101, two phases of program G2, Interzeag AG, Schlieren, Switzerland). All subjects had normal eye examinations, refractive errors with spherical equivalents <5 diopters and astigmatism <2 diopters, normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…However, mean perimetric test durations obtained with both SAP and SWAP tests were not different throughout the menstrual cycle. Mojon and Zulauf [17], in their study on 28 normal subjects aged 21–48 years, showed that the variability within a visual field is similar for SWAP and standard perimetry. Bibawi et al [18]demonstrated that behavioral aspect of the visual field is most evident in the midluteal phase when the left hemisphere is more activated relative to the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
“…However, mean perimetric test durations obtained with both SAP and SWAP tests were not different throughout the menstrual cycle. Mojon and Zulauf [17], in their study on 28 normal subjects aged 21–48 years, showed that the variability within a visual field is similar for SWAP and standard perimetry. Bibawi et al [18]demonstrated that behavioral aspect of the visual field is most evident in the midluteal phase when the left hemisphere is more activated relative to the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
“…If only the MS is considered, it is theoretically possible that the truncated upper threshold combined with the effect of a high false positive rate (which obscures subnormal values from local defects) may collapse the MS into a predetermined region around the normal values for a 20-year-old. However, a recent normal value study [11] has shown that approximately 98% of the normal population are within this limit, reducing the skew to a minimum. It is nonetheless essential to also consider the clinical circumstances, the pattern deviation, the number of false positive catch trial responses, and the reliability indices when interpreting the visual field of an individual patient.…”
Section: Discussionmentioning
confidence: 97%
“…37,38 SWAP on the Octopus 101 perimeter demonstrates remarkably large variability between normal subjects. 39 SWAP is more affected by ocular media absorption than SAP, 38 which can be problematic when assessing elderly patients. Thus, SWAP is not a preferred test for individuals with significant media opacity.…”
Section: Short Wavelength Automated Perimetrymentioning
confidence: 99%